EFFECT OF LEVELS OF PHOSPHORUS AND SODIUM SALTS ON GERMINATION OF WHEAT S 227 - Vyas, K K; Singh, Punjab (Annals of Arid Zone, 2016)
A field experiment was conducted during the year 1969-70 to study the effect of graded levels of phosphorus and sodium salts on germination count of wheat S 227. Treatments consisted of three levels of phosphorus (0.50 and 100 kg P205/ha), three sodium salts (sodium bicarbonate, Sodium Chloride and sodium sulphate) and four levels of salt concentration (0,00, 0.05, 0.10 and 0.15 per cent on soil weight basis). The effect of sodium salts on germination of wheat S 227 was signifant. Deterimental behaviour of the salts was in the order. NaHCO3 > NaCl > Na2S04 Germination decreased significantly 'with increase in concentration of salt from 0.05 to 0.15 per cent as compared to no salts application treatment. Effect of increasing levels of phoshorus on germination Was not. significant.